Purwarupa Ensiklopedi Adat Perkawinan Minangkabau - Trimilanda, Annisa Syntia; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractÂ This paper discusses the making of the prototype of the indigenous encyclopaedia of Minangkabau marriage. The purpose of this paper is to describe the process of making the prototype of the encyclopedia of traditional ceremonies of Minangkabau marriage. The data collected using descriptive research methods with data collection techniques through interviews to adat leaders and community leaders in accordance with the problems studied. Based on the discussion can be concluded the process of making the prototype of the encyclopaedia of traditional ceremony of Minangkabau marriage as follows: (1) data collection, that is technique or way to collect information about traditional ceremony of Minangkabau marriage, (2) make design in the form of chart in product to be made, and (3) the process of making the product in accordance with the work plan containing the basic provisions of a topic that must be developed from the cover making of the book (cover) is the hard skin on the outside of the book containing the title of the book, and accompanied by several supporting images.Keywords: Prototype ofÂ  enscyclopedia , marriage culture, Minangkabau